Gunung Api Purba Balawaian Diinterpretasi Pada Citra Radar - Sidarto Sidarto (Jurnal Geologi dan Sumberdaya Mineral, 2018)
Abstract - The geology ofÂ  Meratus Mountain is relatively complex and still arguable until these day.Its magmatic activity is characterized by variation of igneous and volcanic rocks. Morphology feature of Balawaian paleo volcano can be recognized with radar imagery. Furthermore, validation of rocks constituent is observed directly from the field and hand sample laboratory analysis include the petrography and geochemistry. As the result, the morphology of Balawaian volcano is concluded as a truncated cone and composed by amphibole basalt which assumed come from the tholeiitic magma origin. The volcano intruded the Late Cretaceous - Late Paleocene andesite-basal unit during Late Miocene or Mio-Pliocene (Neogene). The volcano's magma is then interpreted has originate from Late Cretaceous subduction which trapped in the lower mantle and then flowed to the surface by the influence of Balawaian dextral fault pull apart basin.Keyword: Balawaian, radar imagery, amphibole basalt, Meratus, Neogen.